The Impact of Standardization of Livestock Products on the Economy of Farmers and the Local Economy (European Journal of Marketing and Economics, 2023)
There is a strong link between agriculture and the economy. Smallholder farmers are the foundation of the livestock sector and an essential element in building and developing the local dairy value chain, critical to the development of its local economy. Economic growth is necessary for poverty reduction. The main objective of the study is to know the impact of livestock production on the regional economy of Gjirokastra. The result of the study identifies employment generation and income generation as the major benefit of standardized livestock production. The study hereby recommends that the government should take standardized livestock production as one of the major factors contributing to the economy and also put some policies in place in order to encourage farmers to collaborate in this regard. In Gjirokastra, and despite the efforts made since the transition from the communist regime until now, farmers still face many problems that prevent them from participating effectively in the development of the milk value chain. This research study refers to the views of small farmers in the Gjirokastra region about the milk production sector and the problems faced by these farmers. This study also investigates the effect of several factors (ethical factors, tradition, animal welfare, cultural factors, etc.) on the milk value chain. Convergence model was used in mixed method triangular design as a methodology for this research study. As part of the social data, 34 farmers who produce and sell milk and cheese in the Gjirokastra District were interviewed. The results showed the influence of ethical, cultural and traditional factors on the development of the value chain. The results also showed the problems and difficulties faced by small farmers in rural areas, on the one hand, and the gap between these farmers and government and private organizations on the other.
Keywords: standardization, dairy products, value chain, small farmers, Food safety, Gjirokastra District